The complete replicons of 16 Ensifer meliloti strains offer insights into intra- and inter-replicon gene transfer, transposon-associated loci, and repeat elements. Issue 5 (19th April 2018) - Nelson, Matthew; Guhlin, Joseph; Epstein, Brendan; Tiffin, Peter; Sadowsky, Michael J.
Abstract : Ensifer meliloti (formerly Rhizobium meliloti and Sinorhizobium meliloti ) is a model bacterium for understanding legume–rhizobial symbioses. The tripartite genome of E. meliloti consists of a chromosome, pSymA and pSymB, and in some instances strain-specific accessory plasmids. The majority of previous sequencing studies have relied on the use of assemblies generated from short read sequencing, which leads to gaps and assembly errors. Here we used PacBio-based, long-read assemblies and were able to assemble, de novo, complete circular replicons. In this study, we sequenced, de novo- assembled and analysed 10 E. meliloti strains. Sequence comparisons were also done with data from six previously published genomes. We identified genome differences between the replicons, including mol% G+C and gene content, nucleotide repeats, and transposon-associated loci. Additionally, genomic rearrangements both within and between replicons were identified, providing insight into evolutionary processes at the structural level. There were few cases of inter-replicon gene transfer of core genes between the main replicons. Accessory plasmids were more similar to pSymA than to either pSymB or the chromosome, with respect to gene content, transposon content and G+C content. In our population, the accessory plasmids appeared to share an open genome with pSymA, which contains many nodulation- and nitrogen fixation-related genes. This may explain previous observations that horizontal gene transfer has a greater effect on the content of pSymA than pSymB, or the chromosome, and why some rhizobia show unstable nodulation phenotypes on legume hosts.